Bayesian Belief Networks for Integrating Scientific and Stakeholders’ Knowledge to Support Nature-Based Solution Implementation - Scrieciu, Albert; Pagano, Alessandro; Coletta, Virginia Rosa; Fratino, Umberto; Giordano, Raffaele (Frontiers in Earth Science, 2021)
There is a growing interest worldwide on the potential of Nature-based Solutions (NBS) as measures for dealing with water-related risks, while producing multiple co-benefits that can contribute to several societal challenges and to many of the Sustainable Development Goals (SDGs). However, several barriers still hamper their wider implementation, such as mainly the lack of stakeholders’ engagement and the limited integration of stakeholders’ knowledge throughout the phases of NBS design and implementation. This is a crucial aspect to guarantee that the multidimensional implications of NBS are adequately understood and taken into account by decision-makers. Innovative methods and tools for improving NBS design and supporting decision-makers in overcoming the main barriers to implementation, ultimately enhancing their effectiveness, are therefore needed. The present work proposes a combined approach based on the integration of Fuzzy Cognitive Maps (FCM), Hydraulic Modelling (HM) and participatory Bayesian Belief Network (BBN) aiming to facilitate the stakeholders’ engagement and the knowledge integration process in NBS design and assessment. The approach was developed and implemented within the NAIAD project in the Lower Danube demo site, specifically oriented to support the process of the Potelu Wetland restoration. Firstly, FCM are adopted as a Problem Structuring Method for eliciting stakeholders’ risk perception and problem understanding, and for constructing a causal model describing the system as a whole, with specific attention the expected role of the NBS in reducing flood risk and addressing the key local challenges. Secondly, HM is used to analyze the effect of extreme floods starting from the retrospective analysis of a specific event and to model the potential benefits of risk reduction measures. Lastly, a BBN is used to support the model integration process and a scenario analysis with a user-friendly tool. The whole process can be replicated in other areas and is particularly suitable to support an active engagement of stakeholders (both institutional and not) in the process of NBS design and assessment.